Анизотропия молекулярных процессов в атмосфере земли –как новое явление, которое проявляется рядом наблюдаемых эффектов - Делов, И. А.; Слипченко, Н. И.; Леонидов, А. А. (ХНУРЭ, 2008)
The results are presented of numerous measurements performed at different times of a day and season at four different heights using three independent means demonstrating existence of a new phenomenon in the Earth atmosphere, namely, the molecular processes anisotropy revealing itself in a number of the observed effects.
Keywords: анизотропия; анизотропия молекулярных процессов